Sex Ratio at Birth: A Retrospective Audit of the Birth Records of a Nigerian Hospital - Onyiriuka, AN; Ikeanyi, EM (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: The aim was to determine the sex ratio at birth in St Philomena Catholic Hospital (SPCH), Benin City, south-south, Nigeria and to assess its relationship with birth order and maternal age. Methods: In this retrospective cohort study, the records of all deliveries at St Philomena Catholic Hospital (SPCH), Benin City, Nigeria between 1st January, 2005 and 31st December, 2014 (10 years) were retrieved and analyzed. Stillbirths and infants with ambiguous genitalia were excluded in the analysis. Results: The total number of live-births during the 10-year period under review was 13,702 and these consisted of 7,007 males and 6,695 females, resulting in a sex ratio of 104.7:100 (approximately 1.05) at birth. The yearly sex ratios varied from 1.01 to 1.14. The maternal age and the birth order significantly influenced offspring sex ratio at birth (p < 0.001). The highest sex ratio was found among third-birth-order offspring and the lowest was found among offspring of fifth-birth order and above. Offspring of mothers aged 25-29 years had the highest sex ratio and those of mothers aged 40 years and above had the lowest sex ratio. Conclusions: The sex ratio at birth in south-south Nigeria is comparable to values obtained from south-west Nigeria but lower than that obtained from north-west Nigeria. The birth order and maternal age influenced the offspring sex ratio at birth.